2000
DOI: 10.1152/ajpendo.2000.279.1.e11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated hyperglycemia, insulin, and glucagon on endothelial nitric oxide synthase expression

Abstract: Diabetes is associated with endothelial dysfunction and increased risk of hypertension, cardiovascular disease, and renal complications. Earlier studies have revealed that hyperglycemia impairs nitric oxide (NO) production and diabetes causes endothelial dysfunction in humans and experimental animals. This study was designed to test the effects of altered concentrations of glucose, insulin, and glucagon, the principal variables in types I and II diabetes, on NO production and endothelial NO synthase (eNOS) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
99
2
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 59 publications
10
99
2
2
Order By: Relevance
“…It has been speculated that chronic exposure to high glucose could cause the impairment of NO release and/or the increased destruction of released NO following stimulation by PLC-activating agonists [4,34,35]. In the current study, we provide strong evidence that the IP 3 -Ca 2+ -NO cascade pathway is impaired in endothelial cells exposed to prolonged high glucose in a time-and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 66%
“…It has been speculated that chronic exposure to high glucose could cause the impairment of NO release and/or the increased destruction of released NO following stimulation by PLC-activating agonists [4,34,35]. In the current study, we provide strong evidence that the IP 3 -Ca 2+ -NO cascade pathway is impaired in endothelial cells exposed to prolonged high glucose in a time-and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 66%
“…3B). Moreover, diabetic db/db DMVECs treated with 14S,21R-diHDHA produced more vascular endothelial growth factor (VEGF), a potent angiogenic factor (47,48), than control-treated cells (Fig. 3C).…”
Section: Suppressed Formation Of 14s21r-dihdha In Skin Woundsmentioning
confidence: 99%
“…A hallmark of these vascular complications is endothelial cell (EC) dysfunction that is characterised by reduced nitric oxide-dependent phenomena, including vasodilation and protection against leucocyte-endothelial interactions. Studies have shown that hyperglycaemia impairs nitric oxide production [1,2]. Several studies have demonstrated impaired endothelium-dependent vasorelaxation in diabetic humans [3,4] and in experimental diabetic animals [5,6].…”
Section: Introductionmentioning
confidence: 99%